PERANAN BRIGADE MOBIL (BRIMOB) DALAM PENANGGULANGAN AKSI DEMONSTRASI MASSA DI KOTA SORONG BERDASARKAN PERKAP NOMOR 16 TAHUN 2006 - Clementino Lekatompessy; Weron Murary; Raymond R Morintoh (Ensiklopedia Research and Community Service Review, 2026)
Abstract: The purpose of this research is to look at the police as a state tool with duties to maintain security and order, enforce the law, and provide protection, guidance, and services to the community. Proper crowd control actions are very important so that the goal of creating security can be achieved without violating the rights of people taking part in demonstrations. The Chief of Police Regulation Number 16 of 2006 covers procedures for crowd control, the rights and obligations of officers, and limits on the use of force. Uncontrolled actions can risk human rights violations, such as physical violence against participants who might just be expressing their dissatisfaction peacefully. Therefore, it's really important to identify the existing legal limits when it comes to crowd control. The anarchic protest case in Sorong City shows that the potential for social conflict is very high if political issues and policies are not managed properly, but a humanistic and dialogic approach is still needed so that handling it doesn't lead to more casualties. Empirical legal research was carried out by going directly to the research site at Battalion B Pelopor Satbrimob, West Papua Regional Police, Tanjung Kasuari, West Sorong District, Sorong City. Primary data was obtained directly from respondents about the subject being studied through observation and interviews. Secondary data was obtained from official documents, books related to the research subject, while tertiary data provided guidance or explanations for primary and secondary data. The data and information collected from the research on handling mass demonstrations in Sorong City were then analyzed descriptively and qualitatively, which is a method of data analysis by grouping and selecting the data obtained from the research according to its quality and accuracy. The research findings show that the presence of Brimob as an operational control support (BKO) force boosts the local authorities' resilience in handling large demonstrations. Brimob not only carries out enforcement actions but also plays a role in preventing demonstrations from escalating into riots, maintaining public order, protecting the community, and ensuring that citizens can continue their activities safely despite the protest. Brimob acts as a security stabilizer in Sorong, focusing not only on crowd dispersal but also on conflict escalation prevention and community protection. However, this poses significant risks for both protesters and officers who do not follow procedures, such as using tactical vehicles to chase crowds, which can cause casualties and damage the institution's image.Keywords: Handling, Mass Demonstrations, Mobile Brigade, in Sorong City.